The Yield in Teak Selection Forests in Burma - Unwin, R. (Indian Forester, 1937)
Attention is drawn to a contribution by "Sceptic" in the Indian forester for September 1925 on the subject of the Burma Selection System. "Sceptic" expressed his conviction that the irregular teak selection forests were in reality normal in the sense that there is constant relation between the girth classes. Recent examination of enumerations in girth classes 3 to 6 feet and diameter classes 12 to 24 inches has shown that there is solid ground for "Sceptic's" belief and that allotment to sub-periodic blocks bliRed on areas containing an equal number of stock 3 to 6 feet girth, or 12 to 21 inches diameter, gives in practice a much more equal yield than was obtained by the so called Burma Method, which entails knowledge of survival percentages from class to claas and of rates of growth. Actual results uf girdling of a large working circle during the past 30 years are compared with enumerations of 1901-1904 to illustrate the point. Figures from another folling series show that 4inch diameter cladsed from 12 inches up to 24 inches diameter are closely and constantly related and the writer deduces that this relation cannot conceivably hold good up to 24 lnches only. In the helief that it holds throughout the range he uses the proportion of girdlings obtained in the Past in the same cycle to calculate the yield in future. Control will, however, be by area containing equal numbers of stock 12 to 24 Inches diameter.